Meningkatkan Keaktifan Siswa Dalam Pembelajaran Daring Melalui Media Game Edukasi Quiziz pada Masa Pencegahan Penyebaran Covid-19 - Erlis Nurhayati (Universitas Pendidikan Mandalika, 2020)
The study aims to determine the increased activity of learning in online learning through the media of educational Quiziz. This research is a class action study with subjects of grade VII students ' study. 6 SMP N 1 Gangga as much as 23 people. The study implemented 2 cycles, each cycle 2 times the meeting. Each meeting is based on 4 stages, namely planning, implementation, observation and reflection. The implementation of the research stages is slightly different from learning in the classroom because they are conducted separately or students are at home. Based on the results of the study, at a cycle I gained an average student who was active 52.25% with sufficient catagories. While in cycle II obtained average students active 73.9% with high catagori. So from cycle I and cycle II occurred an increase in the activity of 17.65% students. Thus, research can be concluded that educational game media Quiziz can increase the activity of students in online learning during the prevention of the spread of Covid-19 IPS subjects